Online Reading Strategy Use and Gender Differences: The Case of Iranian EFL Learners - Taki, Saeed; Soleimani, Gholam Hossein (Mediterranean Journal of Social Sciences, 2012)
This study investigated the online reading strategies used by Iranian EFL students and the differences between maleand female learners in terms of online reading strategy use. It also made an attempt to answer the question of whether skilledstrategy users in the offline environment are skilled strategy users in the online environment. Participants in this study were 30students (15 males and 15 females) selected from among 50 MA students at IAU University of Shahreza, Iran. The Survey ofReading Strategies (SORS) and Online Survey of Reading Strategies (OSORS) were adapted to the purposes of this study. Theresults indicated that participants used online reading strategies moderately. Problem-solving strategies and global readingstrategies were used the most. The findings revealed while there were no overall significant differences between males andfemales in terms of online reading strategy use, they did differ significantly on a number of individual strategies. The findings alsoindicated that active strategy users in the offline environment were active strategy users in the online environment. The findingshold implications for EFL teachers, students, material developers, and for researchers.